Determinant of Neonatal Mortality in Rural Gorontalo: A Population-Based Case Control Study - St. Surya Indah Nurdin; Zul Fikar Ahmad (Jurnal Promosi Kesehatan Indonesia, 2026)
Background: Neonatal mortality remains a significant public health challenge, particularly in rural areas, where multiple maternal, perinatal, and neonatal risk factors contribute to adverse outcomes. This study aims to identify the determinants of neonatal mortality in a rural setting.Method: A case–control design was employed involving 224 participants (56 neonatal deaths and 168 surviving controls). Data were obtained from maternal and child health records and structured questionnaires. Descriptive, bivariate, and logistic regression analyses were performed to assess factors associated with neonatal mortality.Result: Significant determinants of neonatal mortality included maternal undernutrition (AOR = 3.54), low birth weight (AOR = 6.77), pregnancy complications (AOR = 8.04), intrapartum complications (AOR = 7.39), and neonatal complications (AOR = 9.17). Meanwhile, variables such as maternal age, education level, socioeconomic status, parity, antenatal care attendance, maternal anemia, interpregnancy interval, referral delay, healthcare access, exposure to cigarette smoke, and clean and healthy living behavior were not significantly associated with neonatal mortality. Neonatal mortality in rural areas is primarily influenced by maternal and neonatal factors related to nutrition and complications. Preventive efforts should focus on improving maternal nutritional status, strengthening early detection of pregnancy and intrapartum complications, and enhancing the management of neonatal complications to reduce neonatal mortality.